Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Appendix B - Graphs of Equations - Exercises - Page 427: 47

Answer

Refer to Graph I, Center of the circle = $(3, 1)$ Radius = $\frac{5 – 1}{2}$ = $2$ The center-radius form of the circle equation is $(x – 3)^2$ + $(y – 1)^2$ = $4$
1498130730

Work Step by Step

Refer to Graph I, Center of the circle = $(3, 1)$ Radius = $\frac{5 – 1}{2}$ = $2$ The center-radius form of the circle equation is $(x – 3)^2$ + $(y – 1)^2$ = $2^2$ $(x – 3)^2$ + $(y – 1)^2$ = $4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.